Cost-effectiveness of the New Zealand diabetes in pregnancy guideline screening recommendations. Issue 6 (22nd June 2015) - Coop, Catherine; Edlin, Richard; Brown, Julie; Farquhar, Cindy
Abstract : Objective: To compare the cost-effectiveness of 2 possible screening strategies for gestational diabetes mellitus (GDM) from the perspective of the New Zealand health system, developed as part of a gestational diabetes guideline. Design: A decision analytic model was built comparing 2-step screening (glycated haemoglobin (HbA1c) test at first booking and a 2 h 75 g oral glucose tolerance test (OGTT) as a single test at 24–28 weeks) with 3-step screening (HbA1c test at first booking and a 1 h glucose challenge test (GCT) followed by a 2 h 75 g OGTT when indicated from 24–28 weeks) using a 9-month time horizon. Setting: A hypothetical cohort of 62 000 pregnant women in New Zealand. Methods: Probabilities, costs and benefits were derived from the literature, and supplementary data was obtained from National Women's Annual Clinical Reports. Main outcome measures, screening and treatment costs (NZ2013) and effect on health outcomes (incidence of complications). Results: The total cost for both strategies under baseline assumptions shows that the 2-step screening strategy would cost NZ1.38 m more than the 3-step screening strategy overall. The additional cost per case detected was NZ12 460 per case. The model found that the 2-step screening strategy identifies 12 more women with diabetes and 111 more women with GDM when compared against the 3-step screening strategy. We assessed the effect of changing the sensitivity and specificity of the OGTT. The baseline model assumed that the 2 h 75 g OGTT has a sensitivity and specificity of 95%. The 2-step strategy becomes more cost-effective when the diagnostic accuracy measures are improved. Conclusions: Adopting a 2-step strategy would moderately increase the number of GDM cases detected at the same time as moderately increasing the number of women with false negatives at a significant cost to the health system. Further evidence on the benefits of the 2 different approaches would be welcome.